GENDER INEQUALITY IN THE WORKPLACE IN CORPORATE (International Journal of Food and Nutritional Sciences, 2021)
This study provides a concise overview of the sociological dimensions of genderinequality in the workplace, addressing historical roots, contemporary challenges, and thepivotal role of sociological analysis in understanding and mitigating this complex issue.Gender inequality in the workplace persists as a deeply entrenched societal phenomenon,reflecting historical norms and perpetuated by contemporary structures. This Study delvesinto the multifaceted nature of this challenge, emphasizing its implications for individuals,organizations, and society at large. Historically, gender roles have shaped expectations andopportunities in the workforce, leading to occupational segregation and unequalrepresentation across industries. Despite strides towards gender equality, the gender pay gapremains a stark reminder of persistent disparities in remuneration, rooted in societalvaluations of different types of work and discriminatory practices. The metaphorical "glassceiling" encapsulates the invisible barriers impeding women's progress into leadership roles,highlighting organizational structures and cultural norms that favor traditional masculineleadership qualities. Work-life balance, a crucial aspect of professional life, is intricatelylinked to gender inequality, often exacerbated by unequal domestic responsibilities.Sociologists contribute significantly to the understanding of gender inequality by employingvarious theoretical frameworks and historical analyses. By exploring global perspectives,societal expectations, and the impact of technology, sociological research sheds light on theintricate web of factors influencing workplace dynamics.